Battery interface modification material and modification method thereof
By using volatile materials such as naphthalene, sulfur or iodine to form an ultrathin molecular layer on the battery interface, the impedance problem of the battery interface is solved, the battery performance is improved and suitable for industrial production, and a low-cost and simple operation is achieved.
Patent Information
- Application Number
- CN202310763693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, battery interface impedance problems lead to reduced rate performance of lithium-ion and sodium-ion batteries, and the existing solutions are costly and complex in operation, making it difficult to be applicable to industrial production.
Using naphthalene, sulfur or iodine with a saturated vapor pressure of 0.1 to 30 kPa at 50 to 120°C, an ultrathin molecular layer is formed on the surface of the electrode and/or solid electrolyte through the volatilization and sublimation process under vacuum conditions to reduce the interface impedance .
It improves the wettability of the battery interface, promotes the conduction of ions and electrons, improves the rate performance and capacity retention rate, is suitable for mass production, and reduces cost and operational complexity.
Smart Images

Figure CN119208602A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a battery interface modification material and a modification method thereof. Background Art
[0002] As key components of batteries, the state of the contact interface between electrodes and electrolytes has a profound impact on the transmission of electrons and ions, which in turn affects the battery capacity, rate improvement, and capacity retention. In lithium-ion batteries / sodium-ion batteries, the liquid electrolyte has poor wettability on the electrodes, resulting in the inability of ions in the electrodes to migrate to the negative electrode through the electrolyte. Although all-solid-state batteries avoid the risks of electrolyte combustion and environmental pollution by replacing the electrolyte in liquid batteries with solid electrolytes, they have improved battery safety. At the same time, small-volume thin-film batteries or micro energy storage devices prepared using thin-film deposition technology provide the possibility of powering integrated electronic devices or flexible electronics. However, the introduction of solid-state electrolytes causes poor contact between the electrolyte and electrode interfaces, resulting in large interface contact impedance and increased electron / ion transfer or conduction impedance, which ultimately leads to a reduction in rate performance and limits the capacity.
[0003] In order to solve the problem of electrolyte and electrode interface impedance, in addition to using flexible sulfides to improve ionic conductivity, electrode and electrolyte surface coating can also improve interface wettability and reduce interface impedance. However, surface coating requires the use of expensive thin film deposition equipment (such as atomic layer deposition, magnetron sputtering, thermal evaporation, etc.). Such methods are costly and difficult to apply commercially. In order to solve the problem of interface impedance, liquid phase deposition methods are widely used in industrial production, but such methods are complicated to operate and may cause environmental pollution due to waste liquid discharge. Therefore, it is urgent to explore low-cost and simple-to-operate modification methods and materials suitable for mass production to improve the interface problems of liquid and solid lithium / sodium ion batteries. Summary of the invention
[0004] In order to solve the battery interface impedance problem, the present invention provides a battery interface modification material and a modification method thereof, in view of the problems of high cost and complicated operation process in the prior art solutions.
[0005] A battery interface modification material: the modification material has a saturated vapor pressure of 0.1 to 30 kPa at 50 to 120°C.
[0006] Furthermore, the modifying material is one or more of naphthalene, sulfur or iodine.
[0007] Furthermore, the method of modifying the battery interface using the above-mentioned modifying material includes: placing the object to be modified and the modifying material in a closed environment, inducing the modifying material to volatilize and sublimate, and allowing the modifying material to adhere to the surface of the object to be modified and its pores, wherein the object to be modified is a battery electrode and / or solid electrolyte.
[0008] Furthermore, the electrode modification method is: placing the electrode to be modified and the modification material under vacuum conditions at a temperature of 50 to 120° C. for a period of not less than 8 hours.
[0009] Furthermore, the electrode modification method is as follows: placing the electrode to be modified and naphthalene in a vacuum drying oven, and controlling the vacuum pressure to be no higher than 10 -2 Pa, at a temperature of 50-120°C, maintained for 8-12 hours.
[0010] Furthermore, the modification method of the solid electrolyte is: placing the solid electrolyte and the modification material under vacuum conditions at a temperature of 50 to 500° C. for a maintenance time of not less than 8 hours.
[0011] Furthermore, the battery includes a lithium-ion battery, a sodium-ion battery, a lithium-sulfur battery and a lithium-air battery.
[0012] Furthermore, the electrode is in sheet shape, and the solid electrolyte is in sheet shape.
[0013] A lithium battery, the preparation method of which includes the above-mentioned battery interface modification method.
[0014] A sodium ion battery, the preparation method of which includes the above-mentioned battery interface modification method.
[0015] The present invention provides a battery interface modification material and a modification method thereof, which utilizes gas molecules with high saturated vapor pressure and easy volatilization and sublimation from the surface of the original phase to adhere to the surface and pores of the electrode and / or electrolyte to form an ultra-thin molecular layer, thereby improving the interface wettability and promoting the conduction of ions and electrons at the interface and the bulk, thereby enhancing the interface charge transfer dynamics, maximizing the rate performance and capacity utilization, and at the same time helping to improve the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a graph showing the discharge capacity ratio of the naphthalene-modified lithium-ion battery ternary positive electrode and the unmodified lithium-ion battery provided in Example 1 of the present invention.
[0017] Figure 2 This is a graph showing the capacity retention rate of the naphthalene-modified lithium-ion battery ternary positive electrode and the unmodified lithium-ion battery provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The present invention will be further described in detail below in conjunction with specific embodiments.
[0019] One aspect of the present invention provides a battery interface modification material: the modification material has a saturated vapor pressure of 0.1 to 30 kPa at 50 to 120°C.
[0020] In order to solve the problem of high contact impedance between the electrode and electrolyte interface, that is, the large electron and ion transfer impedance, a modification material with low cost, simple operation process and suitable for large-scale industrialization is proposed in view of the high cost and complicated operation process of the existing solutions. A material with a high saturated vapor pressure of 0.1 to 30 kPa at a temperature of 50 to 120 ° C and easy to volatilize or sublimate into gas is selected as the modifier. The gas molecules generated by the volatilization or sublimation process from the liquid phase or solid phase in a closed environment are attached to the surface and pores of the battery electrode and / or solid electrolyte, thereby improving the wettability of the electrode and electrolyte interface and promoting the rapid transmission of electrons and ions at the interface.
[0021] Optionally, the modifying material is one or more of naphthalene, sulfur or iodine.
[0022] In this embodiment, naphthalene, sulfur and iodine are volatile and sublimable. At the drying temperature of the electrode or solid electrolyte, they can be dispersed in the gas phase and attached to the surface and pores of the electrode or electrolyte to form an ultra-thin coating at the angstrom or nanometer level, which is beneficial to reduce the interface impedance between the electrode and the electrolyte, reduce the ion and charge transfer impedance, and help to improve the capacity.
[0023] Since naphthalene, sulfur and iodine have a saturated vapor pressure of 0.1 to 30 kPa at 50 to 120°C, they are easily volatilized and sublimated, forming a gas phase dispersed in a closed environment, which is conducive to forming a coating layer on the surface and pores of the electrode or electrolyte. In addition, the above-mentioned modifiers can be placed together in a closed container to form a mixed coating layer.
[0024] In another aspect of the present invention, a method for modifying a battery interface using the above-mentioned modifying material comprises: placing an object to be modified and the modifying material in a closed environment, inducing the modifying material to volatilize and sublimate, and allowing the modifying material to adhere to the surface of the object to be modified and its pores, wherein the object to be modified is a battery electrode and / or solid electrolyte.
[0025] Optionally, the electrode modification method is: placing the electrode to be modified and the modification material under vacuum conditions at a temperature of 50 to 120° C. for a period of not less than 8 hours.
[0026] Preferably, the electrode modification method is as follows: placing the electrode to be modified and naphthalene in a vacuum drying oven, and controlling the vacuum pressure to be no higher than 10 -2Pa, at a temperature of 50 to 120° C., for 8 to 12 hours. More preferably, the electrode to be modified and naphthalene are placed in a vacuum drying oven, and the vacuum pressure is controlled to be no higher than 10 -2 Pa, at a temperature of 120°C, maintained for 10 hours.
[0027] Optionally, the modification method of the solid electrolyte is: placing the solid electrolyte and the modification material under vacuum conditions at a temperature of 50 to 500° C. for a maintenance time of not less than 8 hours.
[0028] In this embodiment, increasing the modification temperature is conducive to the volatilization, sublimation and diffusion of the modification material. However, for the modification of the electrode material, too high a temperature (higher than 120°C) will affect the performance of the binder material in the electrode. If the modification temperature is lower than 50°C, the modification material will cover the electrode surface too slowly, so the modification temperature is controlled at 50-120°C; if the modification time is short, the modification material may not cover the pore part well, so the modification time is not less than 8 hours. Experiments on naphthalene-modified electrode materials have shown that when the modification temperature is controlled at 50-120°C and the modification time is 8-12 hours, the discharge specific capacity and capacity retention rate of the battery are steadily improved, so it is preferred to control the modification time to 8-12 hours; vacuuming is conducive to the diffusion of gaseous molecules; experiments have shown that the preferred conditions for naphthalene-modified electrodes are: the vacuum pressure is not higher than 10 -2 Pa, at a temperature of 120°C, maintained for 10 hours.
[0029] For solid electrolytes, the modification temperature can be raised to 500°C. Under vacuum conditions, the temperature range is 50-500°C, and the maintenance time is not less than 8 hours, preferably 8-12 hours, which can achieve the modification of solid electrolytes. The higher the temperature, the more the volatilization and sublimation of the modification material can be utilized. The modification material diffuses in the form of gas molecules in a closed environment, which is conducive to the deposition on the surface of the solid electrolyte and its pores, forming a coating layer with an angstrom or nanometer thickness. After high-temperature baking, the surface bonding force between the molecular layer coating and the solid electrolyte is further improved, and the uniform coating of the ultra-thin molecular layer is achieved.
[0030] Optionally, the battery includes a lithium-ion battery, a sodium-ion battery, a lithium-sulfur battery and a lithium-air battery.
[0031] The modification method of the present invention can be applied to various types of batteries to modify their interfaces due to its simple operation steps, low processing cost and good diffusivity of gaseous molecules.
[0032] Optionally, the electrode is in sheet shape, and the solid electrolyte is in sheet shape.
[0033] The modification method of the present invention has good modification effect when used for sheet-shaped electrodes and / or solid electrolytes, and the performance of the modified battery is significantly improved. When used for modifying powdered electrodes and powdered solid electrolytes, the modification effect is poor. The reason may be that when the powder is piled up, gaseous molecules are difficult to penetrate and modify.
[0034] Another aspect of the present invention provides a lithium battery, the preparation method of which includes the above-mentioned battery interface modification method.
[0035] In another aspect of the present invention, a sodium ion battery is provided, and a preparation method thereof includes the above-mentioned battery interface modification method.
[0036] The present invention provides a battery interface modification material and modification method thereof, which utilizes gas molecules with high saturated vapor pressure and easy to volatilize and sublimate from the surface of the original phase to form an ultra-thin molecular layer attached to the surface of the electrode and / or electrolyte, thereby improving the interface wettability and promoting the conduction of ions and electrons at the interface and the body, thereby improving the interface charge transfer dynamics, maximizing the rate performance and capacity, and at the same time helping to improve the cycle stability. It can be applied to various types of batteries, including lithium-ion batteries, sodium-ion batteries, lithium-sulfur batteries, and lithium-air batteries, etc. The modification method of the present invention is simple to operate, low in cost, and suitable for mass production.
[0037] The present invention will be further described below in conjunction with specific embodiments.
[0038] Example 1 A ternary lithium-ion battery interface modification material and modification method thereof
[0039] Lithium-ion battery: positive electrode material: LiNi 0.88 Co 0.09 Mn 0.03 O2, the negative electrode material is: metallic lithium sheet, the electrolyte is: commercial LiPF6, that is, 1 mol / L LiPF6 is dissolved in EC:DEC:DMC=2:5:3.
[0040] Naphthalene is used as a modification material to modify the ternary positive electrode of the lithium-ion battery. The specific modification method is as follows:
[0041] Weigh 1 g of naphthalene in a watch glass and place it in a vacuum oven. Then place the cut electrode sheet (12 mm in diameter) next to the watch glass containing naphthalene. Then evacuate the vacuum oven to a temperature no higher than 10 -2 Pa, kept at 120 ° C for 10 hours, and then the modified ternary positive electrode was taken out. The modified ternary positive electrode, metal lithium sheet negative electrode and commercial LiPF6 electrolyte were used to assemble a lithium-ion battery, and the performance test was compared with that of the lithium-ion battery assembled with the unmodified ternary positive electrode, metal lithium sheet negative electrode and commercial LiPF6 electrolyte under the same conditions.
[0042] The experimental results show that the discharge capacity and capacity retention rate of the naphthalene-modified ternary positive electrode lithium-ion battery and the unmodified ternary positive electrode lithium-ion battery in Example 1 after 100 charge and discharge cycles at 45°C, 3.0-4.4V, and 1C rate test conditions are as follows: Figure 1 and Figure 2 As shown. As can be seen from the figure, the discharge specific capacity and capacity retention rate of the ternary positive electrode lithium ion battery modified by naphthalene are significantly improved, indicating that the interface impedance of the ternary positive electrode is reduced by naphthalene modification, and the battery performance is improved. In addition, what embodiment 1 adopts is liquid electrolyte, because of the solubility of naphthalene powder in electrolyte, the positive electrode surface after naphthalene modification is in contact with electrolyte, and the naphthalene on the surface will also be dissolved to a certain extent in the electrolyte, if the electrolyte is replaced by solid electrolyte, the naphthalene dissolution problem is avoided, and the reduction effect on the battery interface impedance will be better, and the corresponding modified solid-state battery performance improvement will be better.
[0043] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.
Claims
1. A battery interface modification material: characterized in that: The modifying material has a saturated vapor pressure of 0.1 to 30 kPa at 50 to 120°C.
2. The battery interface modification method according to claim 1, characterized in that: The modifying material is one or more of naphthalene, sulfur or iodine.
3. A method for modifying a battery interface using the modifying material according to claim 1 or 2, characterized in that: include: The object to be modified and the modification material are placed in a closed environment, and the modification material is induced to volatilize and sublime, so that the modification material adheres to the surface of the object to be modified and its pores. The object to be modified is an electrode and / or a solid electrolyte of a battery.
4. The method for modifying the battery interface according to claim 3, characterized in that: The electrode modification method is as follows: placing the electrode to be modified and the modification material under vacuum conditions at a temperature of 50-120° C. for a maintenance time of not less than 8 hours.
5. The method for modifying the battery interface according to claim 4, characterized in that: The electrode modification method is as follows: placing the electrode to be modified and naphthalene in a vacuum drying oven, and controlling the vacuum pressure to be no higher than 10 -2 Pa, at a temperature of 50-120°C, maintained for 8-12 hours.
6. The method for modifying the battery interface according to claim 3, characterized in that: The modification method of the solid electrolyte is: placing the solid electrolyte and the modification material under vacuum conditions at a temperature of 50 to 500° C. for a maintenance time of not less than 8 hours.
7. The method for modifying the battery interface as claimed in claim 3, characterized in that: The batteries include lithium-ion batteries, sodium-ion batteries, lithium-sulfur batteries and lithium-air batteries.
8. The method for modifying the interface of a lithium battery as claimed in claim 3, characterized in that: The electrode is in sheet shape, and the solid electrolyte is in sheet shape.
9. A lithium battery, characterized in that: The preparation method comprises the battery interface modification method according to any one of claims 3 to 8.
10. A sodium ion battery, characterized in that: The preparation method comprises the battery interface modification method according to any one of claims 3 to 8.
